A Review of Psychosocial Factors on Birth Outcomes in Women with Substance Use Disorder in the United States: The Importance of Preventing Relapse During Sustained Remission - Alexandra R. Dailey (University Library System, University of Pittsburgh, 2024)
Infant mortality rate has been an area of concern for the United States for years. Many attributing factors, including psychosocial influences, have been identified. Pregnant patients with substance use disorder have also been shown to experience poor birth outcomes. This study examines trends related to socioeconomic hurdles and mental health in pregnant women with substance use disorder. Databases were searched to find resources that outlined these relationships. After assessing the study designs and associations of fifty-five resources, several patterns were observed, including an increased risk of adverse birth outcomes with higher maternal stress and lower socioeconomic status. In pregnant women with substance use disorder, post-traumatic stress and social stigma resulted in negative effects on mental health. Substance use-related pregnancy anxiety was amplified by triggers that resulted in feelings of fetal detachment and substance cravings. Most literature focused on pregnant patients with active addiction; however, these triggers may have an especially powerful effect on women who become pregnant while in substance use recovery. Studies on remission trajectories indicated a higher mortality risk in people with a history of substance use but have not yet calculated the proportion of women capable of bearing children in this category. This highlights the necessity to develop personalized treatment for pregnant women in sustained remission from substance use disorder to prevent relapse during this crucial time. This population would benefit from a screening tool that assesses for high-risk events like PTSD, psychological stress, and substance use triggers and intervention that includes evidence-based mental health resources.